JUMPA Vol.2 No.2 Juni 2015 PENGARUH HARGA, LOKASI DAN KUALITAS PENDIDIKAN TERHADAP KEPUTUSAN ORANG TUA DALAM MEMILIH JASA PENDIDIKAN: PENGARUH HARGA, LOKASI DAN KUALITAS PENDIDIKAN TERHADAP KEPUTUSAN ORANG TUA DALAM MEMILIH JASA PENDIDIKAN - Darwin Sekolah Tinggi Ilmu Ekonomi Y.A.; Nursiti Sekolah Tinggi Ilmu Ekonomi Y.A.I (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2015)
The aim of this study was to investigate the influence of the price, location and quality of education to the decision of parent to choose the education services and the effect of price, location and quality of education together against the decision of parents to choose the education services on SDIT Ulul Albab Tambun . The population in this study , are all employees of parents who send their chindren to SDIT Ulul Albab totaling 715 people.Metode that is used in determining the number of samples , is to use the formula slovin , so the number of samples in the can , is 88 people . The data used in this study , is a primary data obtained from respondents to the questionnaire , or answer questions about the price, location and quality of education.Hypothesis testing regression showed a significant influence on the price of the decision of parent to choose the education services where t count > t table 5,582 > 1,988 or research hypothesis H1 is accepted .Hypothesis testing regression showed a significant influence on the location of the decision of parent to choose the education services where t count > t table 9,224 > 1,988 or research hypothesis H2 is accepted .Hypothesis testing regression showed a significant influence on the quality of education to the decision of parent to choose the education services where t count > t table 10,094 > 1,988 or research hypothes is H3 is accepted.Multiple regression hypothesis testing X1 X2 X3 on Y indicates there is a positive and significant effect of the price, loction and quality of education to the decision of parent to choose the education services in which F count > Ftable 128,952 > 2,713 or research hypothesis H4 is accepted.